Os saberes tradicionais locais como possibilidades de inserção no ensino de ciências na escola Pedro Reis Ferreira em Parintins - AM - Bruce, Maria Valcirlene de Souza (2015)
The present research, entitled The local traditional knowledge as possibilities of insertion in science education at school Pedro Reis Ferreira in the municipality of Parintins/AM, aims to understand the local traditional knowledge as possibilities of insertion in science education. In this way, we seek theoretical contribution in Brasil (1998), Krasilchik (1987), Carvalho (2009, 2012, 2013), Delizoicov, Angotti e Pernambuco (2011), Diegues (2004), Ferraço (2005), Goodson (2008) and Arroyo (2011), Chassot, (2008, 2011), Fraxe (2007), Almeida (2010), among others. The choice of the theme of the research occurred from concerns of our pedagogical practice elapsed experienced in the city of Parintins-AM, where we observed that even though teachers training in the area of natural sciences, encounter barriers and difficulties, to develop a teaching focused on the discipline, in the sense that it becomes more contextualized, where students can build their knowledge starting from the school reality and connecting them the to their knowledge of every life. So that the objective could be achieved, has the qualitative approach, with the techniques of participant observation with 17 students of the sixth grade of elementary school, semi-structured interviews with the teacher who teaches the discipline of natural sciences, the principal of the school and five students ' parents. Also made use of the field journal to record the perceptions of the researcher during data collection on the site of the research. The data collected were organized from the Central specific categories, and analyzed, having as theoretical contribution to analysis of the content of Bardin (1977) from the specific objectives, enabling the identification of the possibilities of integration of traditional knowledge in science education in that school. The survey results show that the construction of knowledge, from traditional knowledge taught by the fathers to the children, is of paramount importance in the recovery of knowledge historically built through the generations preceding the students. And, to be inserted in science education at school reality, enable a more concrete learning of meanings within the natural laboratory, place of life of students knowledge builders.